Optimizing power sources for smart building sensors: a comparative study of LiSOCL2 batteries under controlled discharge profiles - Ravikumar, Chandana; Vcelak, Jan; Faltus, Martin; Vanek, Jakub; Markevičius, Vytautas (Frontiers in Built Environment, 2025)
Lithium thionyl chloride (LiSOCl2) batteries are pivotal in enabling long-term, maintenance-free operation of smart building sensor networks due to their superior energy density, exceptional shelf life, and reliability in extreme environments. These attributes make them particularly suitable for powering a diverse array of embedded electronic devices within smart infrastructure—including wireless HVAC sensors, high-voltage direct current sensing units, low-power IoT nodes, security and occupancy detectors, structural health monitors, and adaptive lighting or ventilation controllers. This study presents an empirical evaluation of four leading LiSOCl2 battery brands—EVE, Saft, TEKCELL, and TADIRAN—to assess their real-world performance under varying discharge currents, with direct implications for power circuit design in smart building sensor networks. Despite similar datasheet specifications, our findings reveal substantial discrepancies in actual performance, capacity retention, and degradation characteristics. This highlights the need for empirical validation in battery selection, beyond nominal manufacturer ratings, especially when deployed in systems requiring sustained ultra-low power draw over multi-decade lifespans. These discrepancies found underscore the need for accurate battery characterization in energy budgeting, adaptive duty-cycling, and intelligent load management strategies. The findings also inform battery selection for hybrid systems incorporating energy harvesting, enabling sustainable, maintenance-free sensor deployment in energy-optimized building environments. By aligning real-world battery behavior with architectural design choices in sensor systems, our results support the deployment of scalable, sustainable sensor networks in smart buildings. These networks can operate autonomously for 10–40 years, reducing lifecycle maintenance costs and material waste, thereby advancing goals in energy-efficient, digitally optimized building design.